The Relationship between Pregnancy Complications and the Incidence of Anemia in Expectant Mothers - Fitrianti Mohune; Rifzul Maulina; Widia Shofa Ilmiah (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Anemia is a global health problem that often occurs in pregnant women. Inadequate pregnancy spacing can contribute to the risk of anemia. This study aims to analyze the relationship between pregnancy spacing and the incidence of anemia in pregnant women. This type of research is observational analytic with a case-control design. This study was conducted from February to October 2024 at a selected health center in the region. The case-control design was chosen to investigate the causes of anemia during pregnancy, particularly focusing on the effects of pregnancy spacing. The number of samples used was 30 cases, while 30 control cases were selected by simple random sampling from a larger pool of eligible pregnant women. The analysis employed the chi-square test to determine the statistical significance of the relationship between pregnancy spacing and the incidence of anemia. Results showed that 21.7% of respondents had anemia, with a significantly higher prevalence in those with a pregnancy spacing of less than two years. After conducting the chi-square test, the result yielded a significant p-value of 0.002, indicating a strong association between short pregnancy intervals and anemia. This finding highlights the potential risks associated with inadequate pregnancy spacing, emphasizing the importance of family planning and prenatal care in preventing anemia in expectant mothers. The study suggests that adequate pregnancy spacing may reduce the incidence of anemia, thus promoting healthier pregnancy outcomes. Furthermore, it underscores the need for educational programs aimed at raising awareness of the benefits of proper pregnancy planning. Such initiatives would not only help prevent anemia but also improve maternal and fetal health. Comprehensive health policies promoting spacing between pregnancies can have long-term positive effects on maternal well-being.